Do drawing tasks improve monitoring and control during learning from text?. (October 2017) - Schleinschok, Katrin; Eitel, Alexander; Scheiter, Katharina
Abstract: In two experiments it was investigated how drawing as a monitoring task affects self-regulated learning and cognitive load. To this end, participants (Exp. 1: N = 73, Exp. 2: N = 69) were randomly assigned to one of two conditions. In the experimental condition, students were asked to read an expository text on the formation of polar lights consisting of five paragraphs, whereby, after each paragraph, they had to create a drawing of the text's content. In the control condition, students read the same text, but performed no drawing task. In both conditions, students had to give judgments of learning (JoLs) after each paragraph and after reading the whole text as well as rate their cognitive load. Then, they were asked to select paragraphs for restudy. In Experiment 1, participants continued with an assessment of their learning outcomes immediately after their restudy selection, whereas in Experiment 2 they were first given the opportunity to actually restudy the selected paragraphs before working on the posttest. Results of both experiments indicate that JoLs rather than cognitive load predicted posttest performance. Moreover, students in the drawing condition compared with the control condition exhibited more accurate (relative) monitoring in Experiment 1 in that their JoLs were more strongly related to performance. Moreover, JoLs predicted students' restudy decisions in both experiments; however, this effect was by-and-large independent of whether they had to draw. Overall, results hint towards the potential of drawing to support metacognitive monitoring. Highlights: Two experiments investigated the effects of drawing on self-regulated learning. Drawing after learning improved relative monitoring accuracy. Control (restudy decisions) was based on monitoring (JoLs). Drawing did not improve control. JoLs but not cognitive load predicted learning outcomes.